The Effect of Nutritional Counseling on Mother Measures in How to Give Children Stunting Eating in Kampar District Tapung - Yulia Febrianita; Ainil Fitri (Journal of International Conference Proceedings (JICP), 2020)
The problem of developmental and nutritional growth disorders in children under five nationally and even the current global problem is stunting. This type of experimental research uses a quasi-experimental nonequivalent control group design research design. The sample of this study was 66 mothers). The results of this study were a comparison of changes in the mean actions of mothers in feeding children between the control and experimental groups was the mean of the control group 140.6 while the experimental group was 94.8 with a p value